2017
DOI: 10.5901/jesr.2017.v7n2p123
|View full text |Cite
|
Sign up to set email alerts
|

English Language Motivation between Gender and Cultures

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…However, male students have higher integrative motivation than female students. Unlike Al Harthy (2017), he found that female students expressed higher integrative motivation than males.…”
Section: Discussionmentioning
confidence: 81%
“…However, male students have higher integrative motivation than female students. Unlike Al Harthy (2017), he found that female students expressed higher integrative motivation than males.…”
Section: Discussionmentioning
confidence: 81%
“…Wang (2012) reported that CL classes improved achievement motivation among female college students. Female students' integrative motivation and attitudes towards the English language are higher than male students (Al Harthy, 2017). Generally, these findings report that CL enhances females' language learning motivation than males' language learning motivation.…”
Section: The Researcher's Own Experiences On the Implementation Of Comentioning
confidence: 64%
“…The Socio-Educational Model (Gardner, 2005) proposed that motivation and situational anxiety LEMECHA GELETO WARIYO are more important in second language learning. Female students' integrative motivation and attitudes towards the English language are higher than male students (Al Harthy, 2017). A large scale meta-analytic study by Teimouri, Goetze, and Plonsky (2019) reported a strong significant association between language anxiety and second language achievement.…”
Section: Introductionmentioning
confidence: 98%
“…The same tendency of higher positive attitude and motivation for learning French of girls than boys was found by Gardner and Lambert (1972) in their Canadian study. Al Harthy (2017) in his study on male and female students in the Arab world says that females have shown superiority over male students in learning English. Further, the integrative part of motivation was more than male students.…”
Section: Gender Based Differencesmentioning
confidence: 99%